Acute re-entry high-altitude pulmonary edema - Viruez-Soto, José Antonio (2020)
Acute high-altitude pulmonary edema is a potentially life-threatening medical condition. Also known as acute re-entry high-altitude pulmonary edema, it may occur in highland dwellers who return to their hometown after having stayed at a lower-level area. This is the case of a 14 year-old male patient, native to and resident of the city of El Alto (La Paz, Bolivia), located at 4,090 meters above sea level. The patient developed acute high-altitude pulmonary edema when returning from a town at 500 meters above sea level. He required intensive care and showed a favorable evolution.